Introduction of Arabic Vocabulary to Early Childhood through Community Service Program at PAUD An-Nur Serba Jadi IV, Sunggal District, Deli Serdang - manik, wagiman; Hasibuan, Muhammad Syarif Muda; Karo, Tiy Kusmarrabbi; Dongoran, Irham (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
Teaching young children foreign languages, particularly Arabic, optimizes their developmental potential. This community service program aims to implement and analyze effective strategies for introducing Arabic vocabulary that children can memorize and articulate proficiently. The activities are participatory and involve local residents at PAUD An-Nur Serba Jadi IV, Sunggal District, Deli Serdang. The strategies employed include introduction, approaches, routine activities, the use of visual media, memorization through singing and movement, individual and group evaluations, and the provision of rewards. The program results indicate a 53% increase in the recognition of Arabic vocabulary, with a breakdown showing a 12% increase in Cycle 1 and a 65% increase in Cycle 2. The enjoyable learning-through-play method, which aligns with the characteristics of early childhood, has proven effective in enhancing vocabulary recognition and memorization. Recommendations for future community service initiatives include expanding the vocabulary scope, extending the duration of activities, and fostering collaboration with students' parents to create a conducive Arabic-speaking environment for children. Collaboration between academics, education practitioners, and policymakers is also necessary to optimize foreign language education from an early age.